Antibacterial Activity Of Green Sirih Leaves (Piper betle Linn) Against Propionibacterium Acnes - Douglas N. Pareta; Rainhard R. M. Tumiwuda; Silvana L. Tumbel; Wilmar Maarisit; Yessie K. Lengkey; Ferdy A. Karauwan; Mitra W. Timburas (Biofarmasetikal Tropis (The Tropical Journal of Biopharmaceutical), 2025)
Betel is one of the medicinal plants often found around us. Because of its properties as an antiseptic and wound medicine, this plant can be cultivated. This research aimed to determine the antibacterial activity of green betel leaf essential oil against Propionibacterium acnes. This laboratory experimental research used a completely randomized design with three repetitions in five concentration treatments, one positive control and one negative control for Propionibacterium acnes bacteria. The test method used was the agar diffusion method. Data was collected by observing and measuring the inhibition zone on each Petri dish, which was then tabulated. The data obtained were analyzed descriptively. At a concentration of 10µl, green betel leaf essential oil can be an antibacterial agent against Propionibacterium acnes, according to the results of measuring the diameter of the inhibition zone produced.